URGENSI KETERBUKAAN INFORMASI PUBLIK DI PROVINSI NUSA TENGGARA TIMUR BERDASARKAN PRINSIP GOOD GOVERNANCE DALAM PERSPEKTIF HUKUM TATA NEGARA - Jimmy Juandi Tinenti; Saryono Yohanes; Hernimus Ratu Udju (Petitum Law Journal, 2026)
Public information disclosure is a principle underlying public access to information produced or owned by public bodies. In practical reality, although there are regulations and provisions governing public information disclosure, there are still many public bodies in East Nusa Tenggara that have not fulfilled their obligations to provide adequate information to the public. Therefore, the formulation of the problem in this study is how urgent is the public information disclosure in East Nusa Tenggara Province and how is the application of the principle of good governance in constitutional law to the urgency of public information disclosure in East Nusa Tenggara Province. This research is a Juridical-Normative research using Juridical-Normative analysis techniques. The results of the study show that the urgency of public information disclosure in East Nusa Tenggara Province is increasingly apparent, although the Public Information Openness Index score increased in 2023, the impact has not been significant on socio-economic improvements such as poverty rates and the Human Development Index (HDI). The principles of good governance, including transparency, accountability, and professionalism, are key to optimizing public information management. Challenges such as low professionalism in Regional Apparatus Organizations and lack of accountability need to be addressed through training, improving the monitoring system, adopting technology, and aligning local regulations with national standards. These efforts will support the creation of an effective, responsive, and participatory government in inclusive and sustainable development.